A Case of Post-COVID-19–Associated Paracentral Acute Middle Maculopathy and Giant Cell Arteritis-Like Vasculitis. Issue 3 (September 2021) - Jonathan, Go L.; Scott, Fair M.; Matthew, Kay D.
Abstract : Abstract: A 47-year-old man with a history of COVID-19 infection 2 months before presentation, presented with a scotoma of the paracentral visual field of the right eye. After thorough testing and evaluation, a diagnosis of paracentral acute middle maculopathy (PAMM) was established. Two months later, the patient developed temporal headache and jaw claudication. High-dose steroids were initiated, and workup for giant cell arteritis (GCA) was undertaken. The patient experienced resolution of the symptoms within 24 hours of steroid initiation. ESR, CRP, and temporal artery biopsy results were normal, although all were obtained more than 2 weeks after steroid initiation. To the best of our knowledge, our patient represents the first individual to date to potentially implicate COVID-19 in both small and large vessel vasculitis in the ophthalmic setting.